The rule of law and the idea of restorative justice in the handling of children in conflict with the law in the investigation process based on Law No. 11 of 2012 concerning the Criminal Justice System for Children - Abdurrachman, Hamidah (Law Research Review Quarterly, 2016)
This study examines the model of law enforcement applying Law Number 11 Year 2012 Regarding the Criminal Justice System for Children with restorative justice through diversion in the Central Java Regional Police. This research is a multi-year study funded by the Director General of Higher Education with the Contract Agreement Number No. 006 / SP2H / PL / Dit.Litabmas on 5 February 2015. This type of research is empirical, primary and secondary data sources include laws, literature and doctrine. Data analysis was carried out qualitatively. The Central Java Regional Police have implemented Law Enforcement with the Restorative Justice model through Diversi in handling ABH by 29.78%. Constraints in the implementation of Diversi there is no SOP, the time limit is very short, the availability of child investigators in the Polres is still minimal, do not have adequate space for children, do not have child custody space, handling children in conflict with the law has not been a priority unless cases are of concern Public. Besides that, from the victim's side, the mediation became transactional politics.